Proceedings of the 40th International Conference on Software Engineering: Companion Proceeedings 2018
DOI: 10.1145/3183440.3194950
|View full text |Cite
|
Sign up to set email alerts
|

How do community smells influence code smells?

Abstract: Code smells reflect sub-optimal patterns of code that often lead to critical software flaws or failure. In the same way, community smells reflect sub-optimal organisational and socio-technical patterns in the organisational structure of the software community. To understand the relation between the community smells and code smells we start by surveying 162 developers of nine opensource systems. Then we look deeper into this connection by conducting an empirical study of 117 releases from these systems. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
2

Relationship

5
5

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 19 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…According to the survey participants, 51% of the factors that helped in their attraction are social in nature; and 44% of the barriers faced in this process are also human and social ones. The importance of human and social barriers to technical contributions was also observed by Palomba et al [32]. Our findings, therefore, confirm the importance of human and social factors in OSS development.…”
Section: Discussionsupporting
confidence: 91%
“…According to the survey participants, 51% of the factors that helped in their attraction are social in nature; and 44% of the barriers faced in this process are also human and social ones. The importance of human and social barriers to technical contributions was also observed by Palomba et al [32]. Our findings, therefore, confirm the importance of human and social factors in OSS development.…”
Section: Discussionsupporting
confidence: 91%
“…In this respect, our work is unique. As a final note, it is worth highlighting that we preliminarily assessed how community smells influence code smells [139] by surveying developers on such a relation. Our results indicated that community-related factors were intuitively perceived by most developers as causes of the persistence of code smells.…”
Section: Related Workmentioning
confidence: 99%
“…Our findings highlight a prominence of subversive dimensions. The existence and prominence of such dimensions further motivates streams of inquiry around social software engineering [47] and the quality of organizational and community structures [48]- [50] for software engineering.…”
Section: A Discussionmentioning
confidence: 99%